Implementation Evaluation Authentic in Learning History Curriculum 2013 at SMA Negeri 1 Purwareja Klampok - Nurohim, Amin; Ba'in, Ba'in; Suryadi, Andy (Indonesian Journal of History Education, 2019)
The purpose of this research is to 1) to know teachers' understanding of the authentic assessment; 2) know the application of authentic assessment that the teacher has conducted; 3) know teachers' problems in implementing authentic assessment; 4) know the efforts to overcome the obstacles in the implementation of authentic assessment. The method uses a qualitative approach with descriptive methods to obtain the data using interviews, documentary studies, and observations. To test the validity of the data triangulation sources and techniques. Data analysis was performed using analytical models of interaction. The results of this study showed 1) teachers' understanding of authentic assessment of Curriculum in 2013 is still subjective based on personal knowledge; it does not line up with the theory; 2) on the authentic assessment process, teachers have prepared various assessments based on Curriculum 2013, but the implementation is not entirely by the planning on lesson plan; 3) the problems experienced were the number of techniques and instruments that should be implemented, the lack of facilities and infrastructure, and the government regulations were often capricious; 4) efforts that the teachers have conducted are trying every technique, moving classes to obtain adequate facilities and infrastructure, and also keeping in touch with other teachers and curriculum holders.